Hematology 101 Morphology Updates - Bain, Barbara J. (John Wiley & Sons, Incorporated, 2023)
Cover -- Title Page -- Copyright Page -- Contents -- Preface -- Note to the reader -- Acknowledgements -- Abbreviations -- Chapter 1 Malaria - one swallow makes a summer -- Chapter 2 The significance of irregularly contracted cells and hemighosts in sickle cell disease -- Reference -- Chapter 3 Striking dyserythropoiesis in sickle cell anemia following an aplastic crisis -- Chapter 4 A normal mean cell volume does not exclude a diagnosis of megaloblastic anemia -- Reference -- Chapter 5 Prominent Howell.Jolly bodies when megaloblastic anemia develops in a hyposplenic patient -- Chapter 6 A ghostly presence - G6PD deficiency -- Reference -- Chapter 7 G6PD deficiency in patients identified as female -- Chapter 8 The cause of sudden anemia revealed by the blood film -- Chapter 9 Choreo-acanthocytosis -- Reference -- Chapter 10 Lead poisoning -- References -- Chapter 11 Dysplastic neutrophils in an HIV-positive woman -- Reference -- Chapter 12 Help with HELLP -- Chapter 13 Neutrophil dysplasia induced by granulocyte colony-stimulating factor -- References -- Chapter 14 COVID-19 and acute kidney injury -- References -- Chapter 15 Diagnosis of pyrimidine 5' nucleotidase deficiency suspected from a blood film -- Chapter 16 Bone marrow aspirate in Chédiak-Higashi syndrome -- Chapter 17 Phytosterolemia -- Reference -- Chapter 18 Pseudo-Chédiak-Higashi inclusions together with Auer rods in acute myeloid leukemia -- References -- Chapter 19 Botryoid nuclei resulting from cocaine abuse -- References -- Chapter 20 Infantile pyknocytosis -- References -- Chapter 21 Splenic rupture in cytomegalovirus infection -- References -- Chapter 22 A new diagnosis of monoclonal B-cell lymphocytosis with cytoplasmic inclusions in a patient with COVID-19 -- Chapter 23 Pseudoplatelets and apoptosis in Burkitt lymphoma -- References -- Chapter 24 What is a promonocyte?.
Keywords: Blutkrankheit; Blutuntersuchung; Electronic books